Narrative methods for the human sciences - Riessman, Catherine Kohler (California, Sage., 2008)
Offers an overview of qualitative research based on interpreting stories. Designed to improve research practice, this title provides detailed discussions of four analytic methods: thematic analysis, structural analysis, dialogic/performance analysis, and visual narrative analysis. It also presents arguments about validation in case-based research
1 looking back looking forward -- 2 constructing naraatives for inquiry -- 3 thematic analysis -- 4 structural analysis -- 5 visual analysis -- 6 truth and cautions